2012
DOI: 10.1590/s1517-86922012000600014
|View full text |Cite
|
Sign up to set email alerts
|

O treinamento físico aeróbio inibe a sinalização apoptótica muscular esquelética mediada por VEGF-VEGR2 em ratos espontaneamente hipertensos

Abstract: Aerobic exercise training (ET) has been established as an important non-pharmacological treatment for hypertension, since it corrects the microvascular rarefaction and decreases blood pressure. Studies have shown that microvascular abnormalities are directly associated with changes in the vascular endothelial growth factor (VEGF) and VEGF receptor 2 (VEGFR2), as well as with imbalance of apoptotic signaling in hypertension. However, little is known about these mechanisms in hypertension. We hypothesized that E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(54 reference statements)
1
3
0
Order By: Relevance
“…Similarly, Fernandes et al showed that 10 weeks of regular swimming in male rats increased anti-apoptotic proteins of Bcl-2 and Bcl-xl and reduced apoptotic Bad protein. This occurs with Bad phosphorylation and leads to a reduction in the ratio of Bad compared to Bcl-2 (23). The results of the above-mentioned study are consistent with our results, where a reduction was also observed in Mcl-1 gene expression.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, Fernandes et al showed that 10 weeks of regular swimming in male rats increased anti-apoptotic proteins of Bcl-2 and Bcl-xl and reduced apoptotic Bad protein. This occurs with Bad phosphorylation and leads to a reduction in the ratio of Bad compared to Bcl-2 (23). The results of the above-mentioned study are consistent with our results, where a reduction was also observed in Mcl-1 gene expression.…”
Section: Discussionsupporting
confidence: 92%
“…To perform the RT-PCR technique based on the PCR Kit Takara protocol, 6.5 μL of SYBR Green was added to 1 μL of cDNA, and then 0.5 μL of reverse and forward primers was added, and finally, 4.5 μL of the injected water was added to it such that the volume of 13 μL could be obtained. Eventually, the samples were placed in the RT-PCR machine and the device was adjusted according to Table 2, followed by evaluating the results (23).…”
Section: Real-time Polymerase Chain Reaction Techniquementioning
confidence: 99%
“…The RA + AT protocol is characterized by low to moderate intensity and long duration, which effectively increases muscle oxidative capacity. 32,33 The RA + RT protocol requires increasing overload leading to high training loads and is characterized as an intense exercise protocol 34 capable of inducing muscle hypertrophy. 25 The RA + CT1 and RA + CT2 CT protocols 35 aim to promote health or performance benefits with mixed adaptations of aerobic and RT.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, four physical training protocols were applied with different TVs. The RA + AT protocol is characterized by low to moderate intensity and long duration, which effectively increases muscle oxidative capacity 32,33 . The RA + RT protocol requires increasing overload leading to high training loads and is characterized as an intense exercise protocol 34 capable of inducing muscle hypertrophy 25 .…”
Section: Discussionmentioning
confidence: 99%